Legal Protection of Agricultural Land Against Land-Use Changes in Tangerang Regency - Rizkatul Wahdiyah; Diya Ul Akmal; Hastuti Nur Herawati (RESPONSIVE LAW JOURNAL, 2026)
This research aims to determine the legal regulations that provide legal protection for agricultural land. In addition, this research also aims to determine the protection of sustainable food agricultural land in Tangerang Regency. This research uses a normative legal method with a statutory approach, whose data is obtained through literature study. The results show that the legal regulations for the protection of sustainable food agricultural land have been integrated from the national level to the regional level, especially in Tangerang Regency. However, at the implementation level, there are still shortcomings because many agricultural lands are still converted to housing and national and regional development. Especially in Tangerang Regency, it is necessary to implement an integrated information system for sustainable food agricultural land in each region.